E Efektivitas Albendazol Dosis Tunggal terhadap Infeksi Soil Transmitted Helminths (STH) - Sari, Monica Puspa (Universitas Kristen Krida Wacana, 2024)
The problems of worm’s infection is still a problem for Indonesian people, especially children who live in endemic areas with a lack of sanitation and clean water. The two recommended treatment regiments are Albendazole 400 mg and Mebendazole 500 mg. Several studies report that the efficacy of albendazole varies. The aims of literature review is to assess the efficacy of albendazole against STH infections, and the factors that influence the efficacy of albendazole, factors that can increase efficacy and reduce efficacy. The research method used is a literature review with a descriptive approach based on literature from relevant research articles or journals. Library searches were searched via Google scholar, Pubmed, E-journal. The keywords and boolean operators used in the research are albendazole AND Soil transmitted helminths OR cure rate OR egg reduction rate. The CR of a single dose of albendazole against A. lumbricoides reaches 80-100%. 50-54% of hookworm infections occur due to frequent recurrent infections. There were differences in results regarding the CR of T. trichiura 12,8%-66,7% and 80-90%. This difference occurs due to differences in the degree of unfections. Single dose albendazole base on CR and ERR is less effective against T. trichiura infection. Albendazole should be given in combination with other drugs or in extra doses to eliminate STH infections.